CIRCULATING ACTIN-BINDING PROTEINS IN PROGRESSION OF LARYNGEAL AND HYPOHARYNGEAL CANCERS - G. V. Kakurina; E. E. Shashova; O. V. Cheremisina; E. L. Choinzonov; I. V. Kondakova (Сибирский онкологический журнал)
High aggressiveness of laryngeal and hypopharyngeal squamous cell carcinomas dictates the necessity of studying the molecular mechanisms of metastasis. Cancer metastasis is associated with remodeling of the cytoskeleton, which is carried out by actin-binding proteins (ABPs). Currently, there is insufficient data on the feasibility of determining the level of circulating ASBs in lymphogenous metastasis of laryngeal cancer (LC). Material and Methods. Blood serum analysis was carried out in 42 LC patients and 15 healthy volunteers using ELISA kits on a microplate ELISA reader Multiskan FC 100 (ThermoFisher Scientific). Among ASBs, cofilin1 (CFL1), fascin1 (FSCN1), ezrin (EZR), profilin1 (PFN1), adenylyl cyclase associated protein 1 (CAP1) were studied. Statistical processing of the results was performed using the Statistica 6.0 software package. Results. It was shown that the serum level of CAP1 was significantly higher in patients with LC compared with the group of healthy volunteers (p=0.00). As the size of the primary tumor increased, the levels of FSCN1, CAP1 and PFN1 significantly increased. The level of FSCN1 was 10 times higher and the level of CAP1 was 40% higher in LC patients with metastases than in LC patients without metastases. Thus, among the studied ASBs, FSCN1, CAP1, and PFN1 play an important role in the pathogenesis of LC. Conclusion. The results of the serum level of ASB in LC were obtained for the first time, and they determine the fundamental basis for the development of new methods for predicting the development of metastases.